Moral Education in the Cadet Corps of the Dnieper Ukraine in the Second Half of XIX - Early XX Century in the Context of Formation Military Pedagogy as a New Scientific-Practical Field - Komirenko, Yuriy (Pedagogical Discourse, 2013)
The article is based on different sources, which cover pre-revolutionary experience of cadet corps, shows the way how instructions of directorate General of military-educational institutions are followed in Poltava, Kyiv, Odessa and Sumy cadet corps in the second half of XIX – early XX century, which is said in works of general M.Dragomyrov. Within the context of military educational reform of 1860-1870, in spite of the reorganization of form, structure and context of military educational process, the main goal stays to be the same – to prepare regular officers; afterwards the priority was placed on educational process, directed towards the formation of a defined world view, personality traits and moral qualities, necessary for the serviceman professional activity.